2022
DOI: 10.3389/fnmol.2022.947191
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of alpha-synuclein to mitochondrial dynamics and quality control

Abstract: Maintenance of mitochondrial health is essential for neuronal survival and relies upon dynamic changes in the mitochondrial network and effective mitochondrial quality control mechanisms including the mitochondrial-derived vesicle pathway and mitophagy. Mitochondrial dysfunction has been implicated in driving the pathology of several neurodegenerative diseases, including Parkinson’s disease (PD) where dopaminergic neurons in the substantia nigra are selectively degenerated. In addition, many genes with PD-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 198 publications
0
17
0
Order By: Relevance
“…There is a debate about the role of αS in mitochondrial morphology and dynamics, 101 with studies indicating that αS induces mitochondrial fragmentation 92,102,103 particularly when in the form of the PD variant A53T. 104 The underlying mechanisms of αS induced mitochondrial fragmentation are still unknown, with studies pointing to a direct involvement of the αS-membrane interaction.…”
Section: Binding To Other Membranes and Organellesmentioning
confidence: 99%
“…There is a debate about the role of αS in mitochondrial morphology and dynamics, 101 with studies indicating that αS induces mitochondrial fragmentation 92,102,103 particularly when in the form of the PD variant A53T. 104 The underlying mechanisms of αS induced mitochondrial fragmentation are still unknown, with studies pointing to a direct involvement of the αS-membrane interaction.…”
Section: Binding To Other Membranes and Organellesmentioning
confidence: 99%
“…The rotenone-induced animal model reproduces the behavioural and pathological features of typical human PD 7 . This model replicates many aspects of PD, such as iron accumulation in the substantia nigra, systemic mitochondrial dysfunction, oxidative damage, microglial activation, selective nigrostriatal dopaminergic degeneration, L-doparesponsive motor deficits, impaired ubiquitinproteasome function, acidification and mitochondrial translocation of PARK7 (DJ-1) and gastrointestinal dysfunction associated with Alphasynuclein (α-Syn) aggregation and accumulation 8,9,10 . Since PD is mostly sporadic in humans with rare mutations, a study by Xicoy suggested that animal models were preferable to cell models like SH-SY5Y as clinical evidence correlated biochemically also 11 .…”
mentioning
confidence: 88%
“…Significantly, the ACTB and ACTG1 genes are found to be shared among 9 out of the top 10 upregulated KEGG pathways and 18 out of the top 20. Thorne et al have detailed the association between Miro, alpha-Synuclein, and Actin in their study ( 3), adding depth to our understanding of these findings. The majority of the top downregulated KEGG pathways show a direct connection to PD (click on the pathway to see the reference).…”
Section: Healthy Control Single Cells Against Pd Single Cellsmentioning
confidence: 99%
“…Additionally, genetic studies have identified variations in Actin family genes in PD patients, highlighting their potential role as genetic drivers of the disease. Dysregulation of Actin polymerization and depolymerization processes may contribute to the formation of Lewy bodies and the degeneration of dopaminergic neurons ( 3). Understanding the role of the Actin family of genes in PD opens avenues for developing targeted therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%